Genetic diversity of Avena ventricosa populations along an ecogeographical transect in Cyprus is correlated to environmental variables - Constandinou, Stella; Nikoloudakis, Nikolaos; Kyratzis, Angelos C.; Katsiotis, Andreas (My University, 2018)
Avena ventricosa Balansa ex Coss. is considered the C-genome donor of the cultivated hexaploid oat and is a `priority' species for conservation, since it has limited geographic distribution and the only recorded populations in Europe are present in Cyprus. The current study attempts to characterize the genetic structure and fragmentation of the species via the application of genotypic markers. It was revealed that the genetic variety was mainly allocated among the populations collected, since clustering obtained was according to the geographic origin of the samples and the habitat. Species distribution modeling showed that the most important climatic variable defining A. ventricosa distribution is the mean diurnal temperature. Furthermore, significant association of the genetic structure to environmental variables was detected; overall, a negative association to precipitation was confirmed, while significant correlations of genetic structure and the temperature at the time of anthesis and germination were established. The safeguarding of this valuable genetic resource is discussed.
Keywords: Avena ventricosa; Genetic diversity; Cyprus; Genetic variability; Avena